2017
DOI: 10.1016/j.energy.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fuel NO models on the prediction of NO formation/reduction characteristics in a pulverized coal combustion field

Abstract: To investigate the effects of fuel NO formation models on the prediction of NO concentrations in a coal combustion field, numerical simulations for a coal combustion field in a 760 kW test furnace were performed. Three models, those proposed by De Soete, Chen et al. and Mitchell et al. were employed to calculate fuel NO formation originating from volatile matter. The results show that the model proposed by Mitchell et al. reproduces the tendency of the experimental data better than the other two models. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The overall reaction rate of gaseous combustion is calculated using a combined model considering chemical kinetics and eddy dissipation, as shown in Equation 17 [12,18]:…”
Section: Gaseous Combustionmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall reaction rate of gaseous combustion is calculated using a combined model considering chemical kinetics and eddy dissipation, as shown in Equation 17 [12,18]:…”
Section: Gaseous Combustionmentioning
confidence: 99%
“…Since the NO x released from atmospheric coke combustion is mainly NO, and the concentrations of NO 2 and N 2 O are very low [18], only the formation of NO was considered in this study. Before performing the NO prediction, a converged solution of the combustion flow field was calculated.…”
Section: Model Of No X Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The total emission of NOx ultimately depends on the oxidation of fuel-N and the reduction of NO. [5][6][7][8] The research of NOx's generation and discharge in sintering process has drawn much attention in recent years. Studies have shown that sintering parameters such as water ratio, fuel ratio, quicklime ratio and the thickness of bed layer had important influences on the NOx concentration in flue gas.…”
Section: Introductionmentioning
confidence: 99%